Creating welcoming spaces: Indigenous journalism students’ perspectives on programming and representation - Kristy Snell; Gwendolyn Roley (Facts & Frictions)
Our research explores the first-hand experiences of Indigenous journalism students in Canada, examining avenues through which journalism programs can improve their inclusivity and create a more welcoming environment. This analysis is based on 21 semi-structured qualitative interviews with Indigenous students and former students who attended journalism diploma and degree programs between 1990 and 2022. Participants were asked about representation, content, cultural sensitivity, and other factors which could influence the well-being of Indigenous students. In addition, this study incorporates a quantitative component which provides a recent and thorough snapshot of Indigenous representation in Canadian journalism programs. The findings provide insight into some of the challenges faced by Indigenous students studying journalism, including feelings of isolation and racism. Participants also provide suggestions for educators and institutions working to create more welcoming spaces.